Education during the Arab renaissance and its path to the west - Khoury, Loulou Al-Akl (Penerbit Universiti Kebangsaan Malaysia, 2019)
Islam was at the origin of schools, during the Umayyad and Abbasid periods, as every Moslem had to know how to read the Koran. In different regions, namely Spain, public schools were free, and education went beyond the teaching of the Scriptures. Propagating ideas read or heard was equivalent to an aptitude certificate. This approach led to the right of the author and was transmitted to universities in the West as well as the works of ancient philosophers and scientists. When The Christian Front Union disintegrated, alliances with Moslem princes were common. Hence, Arab teachers were in charge of educating the royal children of Aragon, and physicians were called at the bedside of patients among other functions. The school of translation established in Toledo by Bishop Raymond comprised a collection of scientific and literary Arab work that enlightened spirits of European countries. The fall of the Andalusias in the XV century marked the end of a perennial civilization. Yet, students are still taught had not Charles Martel beaten the Arabs, nothing would have survived.